Mather work incentive posters and the rhetoric of scientific management in the 1920s. Issue 1 (1st June 2018) - Hakanen, Ernest A.; Novak, Alison
The Charles Mather work incentive posters of the 1920s promoted the philosophy of scientific management that just ten years earlier the US Congress deemed reductionist and dehumanizing. In a time where the rise of middle management and the growing faith in the powers of capitalism were omnipresent, the posters and rhetoric of scientific management made great sense to those in control of big business. Mather's 78 work posters hung in offices and factories all over the country, and describe what it meant to be efficient, productive and a good member of business society in the 1920s. As a medium, Mather's posters served to create and reinforce workplace practices of managers and leaders that would advance 1920s corporation and society. As propaganda, the posters appealed to worker's attitudes, behaviours, emotions and sense of social belonging. This study evaluates the rhetoric and themes of Mather's 71 posters in the 1926‐27 catalogue (the most popular year for the posters). It finds that in a propaganda-like manner, the posters encourage and discourage workplace behaviours that support management at the expense of workers' thoughts and self-protection in the form of unionism. Further, as Mather worked to create posters that would influence the workplace ecology, his posters dissolved into the environment. The rhetoric used within the posters became adopted by organization leaders and employees, thus facilitating the linguistic transition of 1920s corporate society. An evaluation of these posters lends insight into the history of motivational posters and signs within organizational culture. Today, newer motivational posters are hung in offices around the world, with similar intentions to those of Mather. Because Mather's posters signify the beginning of motivational posters in the modern western organization, studying the originals could help describe transitions in corporate culture.